Global diversity and endemism in Early Silurian (Aeronian) brachiopods. (29th November 2013) - Rong, Jiayu; Cocks, L. Robin M.
<x xml:space="preserve">Abstract</x> Silurian brachiopods of Middle Llandovery (Aeronian) ages are reviewed, and 215 genera are identified here, compared with 109 in the preceding Early Llandovery (Rhuddanian), indicating a recovery‐radiation interval after the end‐Ordovician mass extinction. The chief regions in which they are found are the continents of South China, Avalonia‐Baltica, Laurentia and Siberia, which were all at tropical latitudes with the exception of Avalonia. In addition, the very large superterrane of Gondwana, although with patchy brachiopod distribution, included temperate faunas, as well as subtropical faunas (in Iran and Afghanistan). Aeronian brachiopods greatly increased in diversity, with dominance of four major groups: orthides and strophomenides (which had flourished previously in the Rhuddanian), pentamerides and atrypides (which became dominant in the Aeronian), and many newly evolved taxa, and occupied deeper water and wider ecological niches (level bottom and reef) than those in the Rhuddanian. Each of the continents has some endemic genera, but there is a greater proportion of them in South China, where some groups (such as the pentamerides and atrypides) are more diverse and others, such as the orthides, are much less common than elsewhere. Affinity indices (AI) show that two megaunits can be recognized: South China and Avalonia‐Baltica‐Laurentia (ABL); Siberia seems to have been loosely connected with ABL and even more loosely to South China presumably because of its geographical separation in the Northern Hemisphere. The separation of South China from the other megaunits is further supported by cluster analysis.